If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying y = 3 + -3 + 2 Combine like terms: 3 + -3 = 0 y = 0 + 2 y = 2 Solving y = 2 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Simplifying y = 2
| y/2+3y/2+(y+10)/2=16 | | 4x+3y-2=14 | | z+18=-5 | | 8x-3(x-1)=4(x+20) | | (y+3y+y+10)/2=16 | | 4y+6x=21 | | 7.9x-1=6.9x+3 | | y+3y+y+10=16 | | 2d+11e+8d+11e= | | 7x+17=12x+30 | | (x+x+7)/2=20 | | 9y+4.5x=180 | | -3m=5 | | 9x+4.5y=180 | | 8.25+1.00x=22.5 | | 3/8x=-24 | | 6(2n-5)=4n-3 | | 9(3x-7)-26x=9 | | 29-4x=3x+1 | | 2x+197=9x-13 | | 8.24+1.00x=22.5 | | 15x-6=69 | | 10p+12q=24 | | 2x²+2x²-3x-3=0 | | x=9x-13 | | 9=x+1.5y | | 4(2x-4)+2x=64+3x | | 11-10x=35-31x | | mk+mq=x | | 6:2(1+2)=x | | 38-6x=3x+19 | | x/10=6 |